PENGEMBANGAN MEDIA ULAR TANGGA “ASIK” DALAM MENINGKATKAN AKTIVITAS FISIK PADA SISWA KELAS IV MADRASAH IBTIDAIYAH (Politeknik Kesehatan Kemenkes Bandung, 2021)
This research is motivated by the lack of learning media regarding physical activity. The learning process uses books and video media, other alternative media are still rarely used. Therefore, the snake and ladder media